(untitled) - Hahner, Jeffrey C (New York, 2002)
Speaking clearly: Improving voice and diction
Keywords: English language,Communication,Speech,Voice,English language,Tiếng Anh,Giao tiếp,Diễn văn,Tiếng Anh; Phonetics,Diction.,Âm vị học,Ngôn pháp